PIBID: um estudo sobre suas contribuições para o processo formativo de alunos de licenciatura em matemática da PUC-SP - Tinti, Douglas da Silva (2012)
This study aims to investigate, through the perceptions of three students of the Bachelor's Degree in Mathematics, fellows PIBID Exact - PUC / SP, the contributions of the initial phase of this program for the training process of the subject. A semi structured interview was regarded as an instrument for data collection because it would enable the lifting of these perceptions. Thus, the study is based on a qualitative analysis and interpretation of the perceptions that individuals have expressed regarding the actions taken. To this end we seek theoretical support in the process of Learning Teaching is evident that the Introduction to Teaching as part of this process. By understanding the PIBID is a Public Policy proposed by the Federal Government and intended for Initial Teacher Training, a brief study was conducted by presenting this and other actions that turn to this purpose. We conducted also a literature, considering two major conferences in the area of Mathematics Education, which aimed to assess the contributions that PIBID has provided for the training of future teachers of mathematics. This survey, it emerged that seven contributions were considered in this study, the categories of analysis that guided the analysis of the interviews. (I) Knowing the reality of school: structure, function and dynamics, (ii) collaborative and interdisciplinary experience, (iii) Partnership University - School, (iv) Initial training in order to minimize the "reality shock" (v ) Attractiveness of the teaching profession, (vi) Methodological Resources for Teaching Mathematics and (vii) Encouraging and insertion into the world of scientific research. Armed with the analysis it was found, among other things, that the initial actions contributed to overcome negative preconceptions regarding the public school system and that this experience can contribute to the minimization of reality shock experienced in early years of professional practice